2000
DOI: 10.1021/jp002157j
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Experimental and Theoretical Studies of Adenine, Imidazole, Pyrrole, and Water Non-Covalent Complexes

Abstract: We present both experimental and theoretical gas-phase studies of several noncovalent complexes of elementary molecules of biological interest:  adenine, imidazole, pyrrole, and water. By means of charge-transfer collisions between those complexes and laser-excited atoms, dipole-bound cluster anions are observed. This Rydberg electron transfer (RET) spectroscopic technique is used to experimentally determine the very weak excess electron binding energies of the complex anions. Theoretical calculations which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
50
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 29 publications
(40 reference statements)
2
50
0
1
Order By: Relevance
“…Due to the role of neutral imidazole in both biology 4 and materials science, 5 this preference is rather relevant 6 and has been addressed several times. [7][8][9][10][11] In relation to direct methanol fuel cells, comparison to the case of methanol (m) solvation is of interest. 5,12 Beyond classical hydrogen bonds, imidazole can also bind water via C−H hydrogen bonds.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the role of neutral imidazole in both biology 4 and materials science, 5 this preference is rather relevant 6 and has been addressed several times. [7][8][9][10][11] In relation to direct methanol fuel cells, comparison to the case of methanol (m) solvation is of interest. 5,12 Beyond classical hydrogen bonds, imidazole can also bind water via C−H hydrogen bonds.…”
mentioning
confidence: 99%
“…Rydberg electron transfer spectroscopy suggests imidazole as the hydrogen bond acceptor, but remains ambiguous because of uncertainties in the experimental and calculated excess electron binding energies and dipole moments of the floppy dimers. 9 In contrast, a free jet study of the derivative 4-phenyl imidazole 17,18 only revealed water as a hydrogen bond acceptor, but the influence of the phenyl ring is unclear. Therefore, an independent and unambiguous free jet direct absorption study on the isolated parent compound imidazole appears timely and is provided in this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar complexes are reported by Carles et al using electron transfer spectroscopic techniques and semiempirical calculations. [35] The interaction of protonated imidazole with water was theoretically investigated [36] as well as the interactions of the imidazole dimers with water. [37] In both cases it was found that water preferably interacts with the nitrogen atoms of the imidazole ring.…”
Section: Introductionmentioning
confidence: 99%
“…1 Therefore, IM and imidazole dimer (IMD) have been the subject of several investigations to get information about their intermolecular interactions. [1][2][3][4] Despite its importance, to the best of our knowledge no spectroscopic information concerning the imidazole trimer (IMT) is known. Recently, we have reported infrared spectroscopic studies of IM, IMD and its water complexes (IMW and IMDW) in helium nanodroplets.…”
Section: Introductionmentioning
confidence: 99%